Beyond the Gaze and Well Beyond Wolfenden: The Practices and Rationalities of Regulating and Policing Sex Work in the Digital Age. (20th May 2019) - Scoular, Jane; Pitcher, Jane; Sanders, Teela; Campbell, Rosie; Cunningham, Stewart
Abstract : Drawing on the largest study of the United Kingdom online market in sexual labour to date, this article examines the legal and regulatory consequences as aspects of sex work increasingly take place within an online environment. Our research shows that while governmental policy has not kept abreast of these changes, the application of current laws (which have, since the 1950s, focused on public nuisance and, more recently, trafficking and modern slavery) are pernicious to sex workers and unsuited to recognizing and responding to the abuses and exploitation in online markets in sexual labour. These injustices are likely to be exacerbated if policies and policing do not better align with the realities of these markets in the twenty‐first century. This demands a more nuanced regulatory approach which recognizes that people may engage in sex work of their own volition, but which also addresses conditions of labour and criminal exploitation.